Numerical Study of Lean Combustibility Limits Extension in a Reciprocal Flow Porous Media Burner for Ethanol/Air Mixtures - Henriquez-Vargas, L; Bubnovich, V (Elsevier Ltd, 2015)
Abstract An analytical study by computational simulation in ANSYS FLUENT of a lean mixture of ethanol/air combustion in a porous media burner was performed. A two dimensional mathematical model for filtration combustion was used to estimate the lean combustibility limits (LCL) in a standard one directional porous burner (SISO) and a reciprocal flow burner (RFB) in order to determine LCL variation. The combustion phenomenon was simulated with the continuum assumption for two different porous media: 80% high porosity 20 [ppi] alumina foam and 40% low porosity 5.6 [mm] diameter alumina spheres for the two reactor types. In the SISO burner with filtration velocity ug = [0.1; 0.7] [m/s] minimum equivalence ratio values reach Φmin = [0.05; 0.054] and Φmin = [0.044; 0.048] for alumina foam and spheres, respectively. The results for the RFB operating in the same ug interval indicate that LCL are substantially extended, allowing to incinerate mixtures as low as Φmin = [0.021; 0.027] and Φmin = [0.016; 0.022] for alumina foam and spheres as porous media, respectively. The SISO reactor configuration allows incinerating lean ethanol/air mixtures, but with the limitation that the combustion wave eventually reaches the reactor outlet and is extinguished. The RFB reactor scheme provides a permanent and stable combustion, considering that for times longer than 6000 [s] alumina foam as a porous medium borders instability as the heated zone approaches the reactor s end. Finally, comparing LCL in both reactors, in RFB they are reduced by 50-66% relative to SISO. © 2015 Elsevier Ltd.